2023
DOI: 10.3390/bioengineering10030308
|View full text |Cite
|
Sign up to set email alerts
|

Intracycle Velocity Variation in Swimming: A Systematic Scoping Review

Abstract: Intracycle velocity variation is a swimming relevant research topic, focusing on understanding the interaction between hydrodynamic propulsive and drag forces. We have performed a systematic scoping review to map the main concepts, sources and types of evidence accomplished. Searches were conducted in the PubMed, Scopus and Web of Science databases, as well as the Biomechanics and Medicine in Swimming Symposia Proceedings Book, with manual searches, snowballing citation tracking, and external experts consultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…Nevertheless, the VIF results in our models indicated the non-existence of collinearity or multicollinearity between the predictors. Thus, considering the results obtained in the current study and partially agreeing with previous research in swimmers 45 , triathletes must optimize their efficiency through the stroke variables (i. e. technical skills), trying to maximize the SI values.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the VIF results in our models indicated the non-existence of collinearity or multicollinearity between the predictors. Thus, considering the results obtained in the current study and partially agreeing with previous research in swimmers 45 , triathletes must optimize their efficiency through the stroke variables (i. e. technical skills), trying to maximize the SI values.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, and using multilevel modeling (HLM), dv was not retained as a significant predictor of swimming speed. Recently, it has been reported that the dv may not be the cause of a behavior, but rather a consequence ( Fernandes et al, 2022b , 2023 ). Swimmers can increase their swimming speed in two ways: (i) by generating greater propulsive forces in a more powerful manner (resulting in lower efficiency), or; (ii) by demonstrating greater swimming efficiency ( Peterson Silveira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fadillioglu et al [ 9 ] compared running patterns in novice runners vs. expert runners, and identified the key spatiotemporal and kinematic parameters indicating better running performance. In addition, Fernandes et al [ 10 ] conducted a comprehensive review on whether swimming performance is related to kinematic parameters, i.e., intracycle velocity variations.…”
Section: Evaluation Of Motion Patterns Using Validated Biomechanical ...mentioning
confidence: 99%